Sedimentary deformation relating to episodic seepage in the last 1.2 million years: a multi-scale seismic study from the Vestnesa Ridge, eastern Fram Strait - Cooke, Frances; Plaza-Faverola, Andreia; Bünz, Stefan; Sultan, Nabil; Ramachandran, Hariharan; Bedle, Heather; Patton, Henry; Singhroha, Sunny; Knies, Jochen (Frontiers in Earth Science, 2023)
Seafloor hydrocarbon seepage is a natural fluid release process that occurs worldwide on continental shelves, slopes, and in deep oceanic basins. The Vestnesa sedimentary ridge in the eastern Fram Strait hosts a deep-water gas hydrate system that became charged with hydrocarbons ~2.7 Ma and has experienced episodic seepage along the entire ridge until a few thousand years ago, when seepage activity apparently ceased in the west but persisted in the east. Although it has been documented that faults and fractures play a key role in feeding the seeps with thermogenic gases, the mechanisms controlling seepage periodicity remain poorly understood. Here we integrate high-resolution P-cable 3D seismic and Chirp data to investigate the spatial and temporal evolution of high-resolution fractures and fluid flow features in the west of the Vestnesa Ridge. We characterize sediment deformation using a fracture density seismic attribute workflow revealing two highly deformed stratigraphic intervals and associated small-scale pockmarks (< 20 m diameter). Chronostratigraphic constraints from the region show that two highly deformed intervals are influenced by at least three major climatic events for last 1.2 million years: the Mid-Pleistocene Transition (~1.25 – 0.7 Ma), the penultimate deglaciation (~130 Ka) and the last deglacial warming (~14 – 15 Ka). These periods of deformation appear associated with buried methane-derived authigenic carbonate and are potentially sensitive to shifts in the boundary of the free gas - gas hydrate interface. In addition, our results show shifts (up to ~30 m) in the depth of the base of the gas hydrate stability zone associated with major climatic changes that have enhanced deformation and gas leakage along the ridge. Our results have implications for understanding how changes in eustatic sea level and glacial isostatic loading, through key climatic periods, impacts fracture formation and the control on seepage activity.